Ordklasseproblemer, tilfældet sådan - Skafte Jensen, Eva (LexicoNordica, 2015)
The theories of meaning potential are useful when working with part-of-speech as well as with the meaning of specific lemmas. Words don’t belong to word classes or part-of-speech per se. Rather, they hold the potential to – in specific contexts – enter into one or another class. In this paper, this is illustrated through the example of the Danish word sådan (‘thus’, ‘such’ etc.), a highly polysemous word that easily fits many contexts and meanings.